Radiomics Signature as a Predictive Factor for EGFR Mutations in Advanced Lung Adenocarcinoma - Hong, Duo; Xu, Ke; Zhang, Lina; Wan, Xiaoting; Guo, Yan (Frontiers in Oncology, 2020)
Purpose To develop and validate a radiomic signature to identify EGFR mutations in patients with advanced lung adenocarcinoma. Methods This study involved 201 patients with advanced lung adenocarcinoma (140 in the training cohort and 61 in the validation cohort). A total of 396 features were extracted from manual segmentation based on enhanced and non-enhance CT imaging after image preprocessing. The Lasso algorithm was used for feature selection, 6 machine learning methods were used to construct radiomics models. Receiver operating characteristic (ROC) curve analysis was applied to evaluate the performance of the radiomic signature between different data and methods. A nomogram was developed using clinical factors and the radiomic signature, then it was analyzed based on its discriminatory ability and calibration. Decision curve analysis (DCA) was implemented to evaluate the clinical utility. Results Ten features for contrast data and eleven features for noncontrast data were selected through LASSO algorithm.. The performance of the radiomic signature for contrast images was better than that for noncontrast images in all of the 6 different machine learning methods. Finally, the best radiomics signature was built with logistic regression method based on enhanced CT imaging with an area under the curve (AUC) of 0.851 (95% CI, 0.750 to 0.951) in the validation cohort. A nomogram was developed using the radiomic signature and sex with a C-index of 0.908 (95% CI, 0.862 to 0.954) in the training cohort and 0.835 (95% CI, 0.825 to 0.845) in the validation cohort. It showed good discrimination and calibration (Hosmer-Lemeshow test, P = 0.621 for the training cohort and P = 0.605 for the validation cohort). Conclusion Radiomics signature can help distinguish between EGFR positive and wild type advanced adenocarcinomas.